Asymmetric Threshold Cointegration and Nonlinear Adjustment between Oil Prices and Financial Stress - Mighri, Zouheir Ahmed; Alsaggaf, Majid Ibrahim (International Journal of Energy Economics and Policy, 2019)
This paper attempts to estimate the relationship between oil prices and financial stress using weekly data for the period December 31, 1993 to July 15, 2016. The analysis is carried out using the cointegration framework. Both the linear and non-linear models for cointegration and related error correction models are estimated. The paper finds the threshold cointegration model more suitable than the linear cointegration models. It finds evidence of asymmetry in the adjustment process to equilibrium. It also finds that regimes with negative (below the threshold) changes of deviations adjust much faster than regimes with positive (above the threshold) changes of deviations, especially during a crisis period. Also, bi-direction causality is reported between the two variables. Keywords: Threshold cointegration, asymmetric adjustment, asymmetric error correction, financial stress, oil prices, financial crisis. JEL Classifications: C22, C32, C58, G1. DOI: https://doi.org/10.32479/ijeep.7643